2020
DOI: 10.3390/app10165397
|View full text |Cite
|
Sign up to set email alerts
|

Phytoremediation of TSS, NH3-N and COD from Sewage Wastewater by Lemna minor L., Salvinia minima, Ipomea aquatica and Centella asiatica

Abstract: The rapid growth of industries has resulted in wastewater generation containing different organic and chemical substances channeled into the water body. This causes the arising of water pollution issues in many regions. The phytoremediation method was introduced in the process of treating water pollution as it is low cost and environmentally friendly. Lemna minor, Salvinia minima, Ipomoea aquatica and Centella asiatica were chosen in this study because they have tolerance to various pollution conditions and ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 28 publications
(5 citation statements)
references
References 51 publications
1
4
0
Order By: Relevance
“…In the present study, the higher BOD and COD levels for T3 and T4 treatments resulted in lower DO levels for the same treatments. Similar results were found by Abdul Aziz et al [56] who reported that the increase in BOD and COD indicated higher organic matter in the water which reduce the level of DO. However, the BOD (1.96-5.22 ppm) for all treatments in the present study were lower than those levels recorded by Menaga et al [57] and Zaki et al [58] for Nile tilapia (Oreochromis niloticus) reared in biofloc systems (6.30-6.85 and 18.15-27.88 ppm, respectively).…”
Section: Discussionsupporting
confidence: 89%
“…In the present study, the higher BOD and COD levels for T3 and T4 treatments resulted in lower DO levels for the same treatments. Similar results were found by Abdul Aziz et al [56] who reported that the increase in BOD and COD indicated higher organic matter in the water which reduce the level of DO. However, the BOD (1.96-5.22 ppm) for all treatments in the present study were lower than those levels recorded by Menaga et al [57] and Zaki et al [58] for Nile tilapia (Oreochromis niloticus) reared in biofloc systems (6.30-6.85 and 18.15-27.88 ppm, respectively).…”
Section: Discussionsupporting
confidence: 89%
“…The reduction in COD was obtained because Pistia stratiotes L. and Salvinia molesta D. Mitch underwent the process of photosynthesis. Pistia stratiotes L. and Salvinia molesta D. Mitch's photosynthesis activity increases water's dissolved oxygen, thus stimulating aerobic conditions in the domestic wastewater in favor of aerobic bacterial activity to reduce BOD and COD levels (Abdul Aziz et al 2020).…”
Section: Bod and Codmentioning
confidence: 99%
“…In spite of the economic and ecological damage in inflicts, S. minima have a significant potential to be used in phytoremediation due to its rapid growth, adaptation to different climatic conditions, and tolerance to contaminants [70]. The species has already been identified as a phytoremediator of sewage treatment water, reducing the content of total suspended solids [109], heavy metals such as chromium [71,110], lead [111], cadmium, nickel, and zinc [112], and herbicides such as atrazine [113].…”
Section: Eichhornia Crassipesmentioning
confidence: 99%